Experimental dynamic characterization of friction brace dampers and application to the seismic retrofit of RC buildings. (1st September 2021) - Saingam, Panumas; Matsuzaki, Ryota; Nishikawa, Koki; Sitler, Ben; Terazawa, Yuki; Takeuchi, Toru
Highlights: Device-level tests of friction brace dampers with five different friction materials. Investigated cyclic, amplitude, velocity, and temperature friction dependencies. Developed a non-iterative, strength-based equivalent linearization design method. Method is effective for retrofit of RC moment frames with friction brace dampers. Compared friction and buckling-restrained brace retrofits using time history analysis. Abstract: Previous earthquakes have caused extensive damage to reinforced concrete (RC) structures with insufficient lateral force resistance or energy dissipation capacity. There is a need to retrofit vulnerable existing RC buildings, particularly those not originally designed for seismic effects or designed to an outdated seismic specification. This study investigates the use of friction dampers as displacement-dependent energy dissipation devices to retrofit RC moment frame structures. First, an experimental program was conducted to characterize the dynamic behavior of friction brace dampers with several different materials, finding that a sintered metal compound provided a stable friction coefficient of 0.4. A strength-based equivalent linearization design procedure was then developed based on the required friction slip force and considering the cracked state of the existing RC structure. A four-story RC school building was then designed using the proposed retrofit design method, validated using nonlinear response history analysis and compared to a previous retrofit scheme that employed buckling-restrained braces (BRBs) and a stiffness-based equivalent linearization design method. The analysis results suggest that the proposed retrofit design method and friction brace dampers are effective in reducing the maximum story drift.